Rule of law in the EU : 30 years after the fall of the Berlin Wall - Bakardjieva Engelbrekt, Antonina; Moberg, Andreas; Nergelius, Joakim (Oxford : Hart, 2023)
"This book looks at how successful the European project can be judged to have been over the last generation. The 30th anniversary of the Berlin Wall marked a natural moment of stock taking and assessing how the world has evolved since then. The European Union, as much as any institution, could benefit from such introspection. This collection does just that; looking at the key changes in the last 30 years and assessing the Union's success or otherwise at responding to them. Addressing questions such as accession, the enlarged Union, enforcement and uncertainty in the European project, a team of experts gives its reasoned verdict"--
Rule of Law in the EU 30 years after the fall of the Berlin Wall : taking stock and looking ahead / Antonina Bakardjieva Engelbrekt, Andreas Moberg, and Joakim Nergelius -- Rule of law problems as problems of democracy / Leonard Besselink -- Illiberal constitutionalism in East-Central Europe / Gábor Halmai -- Why the rule of law can never be part of an 'illiberal' democracy / Joakim Nergelius -- Legacies of socialist constitutionalism : the Eastern European judiciary / Zdenek Kühn -- Legal reasoning in Central and Eastern Europe from a historical perspective / Katalin Kelemen -- The Council of Europe as an antechamber to the European Union / Daniel Tarschys -- The role of the Venice Commission in strengthening the rule of law / Iain Cameron -- The eastward enlargement as a driving force and testbed for rule of law policy in the EU / Antonina Bakardjieva Engelbrekt -- The rule of law in Italy under the power of populism, and its Impact on the future of the EU : what the pandemic crisis can teach us : some reflections on populism, Europe, the rule of law and fundamental rights during the time of quarantine in Italy / Valentina Colcelli -- The European rule of law standard, the Nordic states, and EU law / Graham Butler -- The rise of procedural rule of law in the European Union - historical and normative foundations / Xavier Groussot and Anna Zemskova -- The European Commission and the EU rule of law policy / Anna Perego -- Respect for the rule of law : some thoughts on the European Parliament's perspective / Linda Stefani and María José Martínez Iglesias -- Can we expect compliance with the rule of law without the rule of law? / Andreas Moberg.
Sisältää bibliografisia viitteitä ja hakemiston.
Kuvailun perustana verkkoaineisto (bloomsburycollections.com, katsottu 12.12.2023).
Keywords: Rule of law -- European Union countries; Berlin Wall, Berlin, Germany, 1961-1989; oikeusvaltio; oikeusvaltio -- Eurooppa; oikeusvaltio -- EU-oikeus; demokratia -- EU-maat; liberalismi -- EU-maat; oikeusvaltio -- itäinen Keski-Eurooppa; laillisuusperiaate -- EU-maat; e-kirjat